Usage of Various Library Software Modules in Engineering Colleges Libraries of Vidarbha Region - Mr. Gautam A.Wani1 & Dr. Sudhir G. Astunkar2 (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This study conducts a survey of engineering college libraries in Vidarbha that have automated their operations and services. The study is limited to the automated libraries of engineering colleges in the Vidarbha region. It displays the status of the software packages utilized in the libraries. The paper also discusses the benefits and drawbacks of library automation. The current focus is on the library automation dilemma and the future of automation. This paper also looks at the performance status of library software modules. The study is based on personal observations and data collecting using questionnaires and personal interviews.